2013
DOI: 10.1093/infdis/jit310
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Minority Drug-Resistant HIV-1 Variants in Primary HIV-1 Infection

Abstract: Drug-resistant HIV-1 MVs can be transmitted. To what extent the origin-transmission vs sporadic appearance-of these variants determines their impact on ART needs to be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
(51 reference statements)
1
27
0
Order By: Relevance
“…This patient participates in the Zurich Primary HIV Infection (ZPHI) study, which is an observational, open label, non-randomized, single center study (www.clinicaltrials.gov; ID NCT00537966) (21,22). Written informed consent was obtained from the patient prior to inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…This patient participates in the Zurich Primary HIV Infection (ZPHI) study, which is an observational, open label, non-randomized, single center study (www.clinicaltrials.gov; ID NCT00537966) (21,22). Written informed consent was obtained from the patient prior to inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Using ultrasensitive techniques, such as deep sequencing or allele-specific PCR, several studies have reported a high prevalence of "transmitted" minority DRM among the ART-naive population (6)(7)(8). The exact origin and clinical relevance of these minority variants carrying DRM are still debated (1,5,(8)(9)(10). We previously performed deep sequencing to detect minority DRM in blood plasma collected from 32 HIV-infected individuals during primary infection, and we found that most low-frequency DRM in our cohort were likely identified because of methodological errors or were a consequence of error-prone HIV replication in the recipient (11).…”
Section: Importancementioning
confidence: 99%
“…All HIV-1 infected individuals enrolled in this study were cared for at the Division of Infectious Diseases and Hospital Epidemiology, University Hospital Zurich and are participating in the Swiss HIV Cohort Study [12], and/or the Zurich Primary HIV Infection Study (ZPHI) [13,14]. The protocol for this study has been reviewed and approved by the ethics committee of the University Hospital Zurich and written informed consent was obtained from all participants.…”
Section: Ethics Statement and Participant Recruitmentmentioning
confidence: 99%